Effects of pacing strategies on the running motion of male 800 meter runners - Kadono, H.; Ae, M.; Enomoto, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of this study was to investigate the effects of different pacing on running motion for male 800 m runners in official competitions. Ten male 800m runners were videotaped (60Hz) from the side positioned the marks of 150m (1st mark), 350m (2nd mark), 550m (3rd mark) and 750m (4th mark) of the 800m race. Kinematics and Kinetics variables were calculated. We divided ten subjects into two groups: Positive-type (POS) which consisted of five subjects with the fastest average running velocity of the 1st and 2nd marks running velocity (running velocity), Negative-type (NEG), which consisted of the five other subjects. In POS, the running velocity, the stride length per height and the shank angular velocity of the support leg were significantly decreased along the race, and the trunk inclined forward than NEG. However, the hip extensor torque, power and the knee flexor torque at the late recovery phase did not decrease. In NEG, the running velocity, the relative step frequency, the hip flexor torque at the early recovery phase, the hip extensor torque and the knee flexor torque at the late recovery phase were significantly increased at the late half of the race. The thigh and shank angular velocity of the support leg were maintained. It was concluded that the running motion of 800 m runners were affected by the pacing strategy.